Effect of Piper betle Leaf Powder Supplementation on Improving the Productive Performance of Broiler Chickens (Ross 308) Exposed to Oxidative Stress Induced by Hydrogen Peroxide - Hayfaa Mohammed Salih (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2026)
The study was carried out at the broiler chicken farm of the Animal Production Unit, College of Medicinal and Industrial Plants, University of Kirkuk, Iraq, during the period from the 4th of September 2025 to the 8th of October 2025. The study was conducted to evaluate the effect of Piper betle leaf powder supplementation on the productive performance of broiler chickens (Ross 308) subjected to oxidative stress induced by hydrogen peroxide. The experiment was conducted using a total of 150 one-day-old broiler chicks of the Ross 308 strain. The chicks were weighed and randomly allocated to the treatments. The treatments were as follows: T1: control treatment; T2: control + 0.4 ml/L hydrogen peroxide in drinking water; T3: control + 0.4 ml/L hydrogen peroxide + 0.75 g/kg feed of Piper betle powder; T4: control + 0.4 ml/L hydrogen peroxide + 1 g/kg feed of Piper betle powder; T5: control + 0.4 ml/L hydrogen peroxide + 2 g/kg feed of Piper betle powder. The results revealed that the supplementation of Piper betle powder significantly improved the productive performance of the broiler chickens subjected to oxidative stress induced by hydrogen peroxide, as the treatments that contained the plant powder showed significant improvements in the productive performance parameters compared to the control and hydrogen peroxide treatments. Therefore, it can be concluded that the dietary supplementation of the broiler chickens with the plant powder may enhance their productive performance under oxidative stress conditions, which may be reflected in the improvements in the body weight gain and the reduction in the feed conversion ratio.